2019
DOI: 10.1016/j.ebr.2019.100338
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping demyelinating syndrome and anti-N-methyl-d-aspartate receptor encephalitis with seizures

Abstract: Anti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis, the most recognized type of autoimmune encephalitis, manifests with rapid cognitive decline, psychosis, and seizures that develop in 78–86% of patients. Recently, anti-NMDAR encephalitis was reported in association with demyelinating diseases which are accompanied by a characteristic clinical phenotype, imaging abnormalities, and the presence of antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) in bodily fluids. The patient presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Seizures and cortical/leptomeningeal encephalitis has been described in MOGAD patients who are NMDA-R-IgG negative, 1,22 anti-NMDA-R-IgG encephalitis, 23 and GFAP-IgG meningoencephalitis, 24 thus these clinical and radiological findings are not specific for dual-positivity. Nonetheless, the frequency of these features in our dual-positive MOG-IgG1+/ NMDA-R-IgG+ cohort, similar to other reports, 18,25 suggests that clinicians should consider serological screening for MOG-IgG1 and NMDA-R-IgG in patients presenting with encephalopathy, seizures, and/or cortical/leptomeningeal encephalitis.…”
Section: Discussionsupporting
confidence: 90%
“…Seizures and cortical/leptomeningeal encephalitis has been described in MOGAD patients who are NMDA-R-IgG negative, 1,22 anti-NMDA-R-IgG encephalitis, 23 and GFAP-IgG meningoencephalitis, 24 thus these clinical and radiological findings are not specific for dual-positivity. Nonetheless, the frequency of these features in our dual-positive MOG-IgG1+/ NMDA-R-IgG+ cohort, similar to other reports, 18,25 suggests that clinicians should consider serological screening for MOG-IgG1 and NMDA-R-IgG in patients presenting with encephalopathy, seizures, and/or cortical/leptomeningeal encephalitis.…”
Section: Discussionsupporting
confidence: 90%
“…Most reports of patients with co-occurrence of MOG-Ab and anti-NMDAR-Ab have shown that anti-NMDARe may develop initially, followed by MOG-AD [ 10 ] ; however, patients with the opposite occurrence [ 11 ] or repetitive onset of anti-NMDARe attacks with no MOG-AD attacks (positive MOG-Ab just being a bystander) have also been reported. When a patient is simultaneously positive for MOG-Ab and anti-NMDARe-Ab, the clinical presentation can be either sequential anti-NMDARe and MOG-AD attacks (or vice versa), [ 10 ] single attack, [ 12 14 ] or a mixed attack.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with FLAMES responded to high dose steroids with resolution of FLAIR changes. Of note, a number of patients developed ON either before or after seizures (56,58,59). Thus, the emergence of seizures in the context of ON or focal brain inflammatory lesions should prompt testing for MOG-Ab (52).…”
Section: Acute Disseminated Encephalomyelitis (Adem) and Other Cerebrmentioning
confidence: 99%